Study of Microplastic Abundance in Animal Fish (Stolephorus Sp) With Microplastic Content in Stunting Clown's Breast Milk: Study in Kragan District, Rembang Regency - Mufia, Maziyyah; Nurika, Globila (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
This study, conducted in Kragan District, investigated the prevalence of microplastics in Stolephorus sp. and their occurrence in the breast milk of stunted infants. Microplastics, emerging as a global oceanic pollutant, pose significant challenges due to their small size and potential impacts on marine and human health. The study focused on their possible transfer to infants via breast milk, raising concerns about associated health risks, including toxicity and infection. Stunting, a critical health issue affecting 14% of Rembang Regency's population, provided the backdrop for this research. The study included all Stolephorus Sp. Sold in Kragan Subdistrict and collected breast milk samples from 11 stunted infants. Employing a descriptive quantitative approach with a case study design, the researchers utilized total sampling based on predefined criteria. Analysis revealed microplastics in both Stolephorus Sp. and breast milk, predominantly as fibers and filaments in black and blue colors. Particle sizes varied widely, with Stolephorus sp. containing 1.00–2.13 particles per specimen and breast milk containing 0.20–3.00 per milliliter. The study identified a correlation between microplastic abundance in Stolephorus sp. and its presence in breast milk among stunted infants. However, no correlation was found between Stolephorus sp. Consumption frequency and microplastic levels in breast milk. These findings underscore the potential pathways of microplastic exposure to infants and highlight the need for further investigation into their health impacts, particularly among vulnerable populations. Future research should continue exploring these dynamics to understand better and mitigate the risks associated with microplastic contamination in food chains and human health.